Factor Endowment Change and Comparative Advantage: The Case of Japan, 1956-1969 - Heller, Peter S. (The Review of Economics and Statistics, 1976)
IT has long been recognized that a country's relative factor endowment will strongly influence the focus of its comparative advantage in international trade. Within the context of the postwar Japanese economy, this paper will consider the impact of a rapid change in factor endowment on the structure of comparative advantage. Several questions will be addressed. In 1954 Japan was a labor-abundant economy,' midway in the factor endowment spectrum between the developed (MDCs) and the less developed (LDCs) economies. A dualism in its economy and trade structure prevailed. Has the rapid erosion of its labor abundance affected the technological character of its trade? As Japan's factor endowment has converged toward that of the MDCs, has the dualism in its trade structure been similarly eroded? In section I we shall briefly describe the structure of Japan's economy during the period and the change that occurred in its factor endowment. Section II will discuss the Leontief methodology used in evaluating the technology of a trade bundle, and some of the index number problems that arise when this methodology is applied in a dynamic context. In section III the change in the technology of exports and imports over the period is examined. In section IV we examine the allocative efficiency of Japan's export structure.